Production performance and water quality of Caulerpa lentillifera with fermented fruit vegetable fertilizer - Supriyono, Eddy; Chrisliana, Chrisliana; Puji Hastuti, Yuni; Lila Antara, Kadek; Ee Ling, Yong; Nurussalam, Wildan (Indonesian Society of Scientific Aquaculture (ISSA), 2024)
The use of fermented vegetable and fruit waste (FVF) based fertilizers as an effort to reduce waste has the potential to be used to support aquaculture activities. This study aims to evaluate the effectiveness of Caulerpa lentillifera cultivation with the addition of fertilizer based on fruit and vegetable waste fermentation on water quality parameters and production performance. The experimental design used was a completely randomized design with three replications for four different doses of FVF fertilizer treatments, namely 0, 0.05, 0.1, and 0.2 µl/L. This study used an initial weight of 500 g which was reared in a concrete tank with a capacity of 1000 L for 30 days growth period. The results showed that the use of FVF of 0.1 µl/L gave a better net harvest weight (p<0.05), namely 0.08 ± 0.06 kg. Keywords: Caulerpa lentillifera, fermentation, fertilizer, seaweed, waste ABSTRAK Penggunaan pupuk berbasis fermentasi limbah sayur dan buah (FVF) sebagai salah satu upaya pengurangan limbah memberikan potensi sebagai larutan pendukung kegiatan budidaya. Penelitian ini bertujuan untuk mengevaluasi efektivitas budidaya Caulerpa lentillifera dengan penambahan pupuk berbasis fermentasi limbah buah dan sayur terhadap parameter kualitas air dan kinerja produksi. Rancangan percobaan yang digunakan adalah rancangan acak lengkap dengan tiga kali ulangan pada empat perlakuan pupuk, yaitu 0, 0.05, 0.1, dan 0.2 µl/L. Penelitian ini menggunakan bobot awal 500 g yang dipelihara dalam bak beton berkapasitas 1000 L. Hasil pengamatan menunjukkan bahwa penggunaan FVF sebesar 0.1 µl/L memberikan bobot panen bersih yang lebih baik (p<0.05) yaitu 0.08 ± 0.06 kg. Kata kunci: Caulerpa lentillifera, fermentasi, limbah, pupuk, rumput laut